PARTISIPASI MASYARAKAT DALAM PEMBANGUNAN DI DESA BUO KECAMATAN LOLODA KABUPATEN HALMAHERA BARAT - Taluke, Ofandres; Lumintang, Juliana; Tumiwa, Juliana (HOLISTIK, Journal Of Social and Culture, 2018)
Be an integral part of rural development, national development of the means, hence a broad-based approach to development villages could not have been on the talk in full that requires multi dimensional sectoral approach and multi to refute the to be obtained a whole description from a variety of factors that affect its implementation and an effect its consequences in the development of other sectors. So that the development runs on a continuous basis and being the force which bubbling through our society itself, so it takes a lot especially with regard to the establishment of a village community efforts to get to participate directly in village of various development activities.In village development there should have been the development monitoring is part of the participation of the community. Supervision is not solely the task of the government only, but also the responsibility of society itself, thereby avoiding several biases to the development of the that existed in the village.One of the maters in the process of the village administration is how build or government created a mechanism that can develop its mission in realizing prosperous society in purpose of creating .The government has to make the construction is based on community aspirations, and provide public services in the most of it.Although there is still barriers small in development and directing the participation of the Buo village, and in fact overall it can be said that the public participation the village has quite inadequate in implementing the project village or rural development.Keywords: Â development, participation, implementation